Filling the Position of Constitutional Court Judge and its Corraletion With the Independence of Judges (Comparative Study of Some Countries) - M Beni Kurniawan (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2018)
Abstract.This article explains how to fill the position of judges of the Constitutional Court in Indonesia by comparing the mechanism of filling the office of judges of the Constitutional Court in several countries in the world. This study also conducted a study on the correlation of filling the position of judges of the Constitutional Court with the independence of judges of the Constitutional Court in carrying out its functions and authority. This article concludes that there are three ways of recruitment of constitutional judges applicable in some countries. First mentioned, the single body mechanism, the appointment mechanism, the executive may determine all members of the Constitutional Court without further supervision by the legislative branch. Second, cooperative appointment mechanisms model; the appointment of this model calls for cooperation between institutions in determining the composition of a court or similar organ. Third is a representative reproduction model, this model involves a number of state institutions. For example, in Italy three of the nine constitutional justices are filed by the President, three by parliament, and three by the Supreme Court.Keywords: Filling the Position of Judge of the Constitutional Court, Independence, Comparison Abstrak. Artikel ini menjelaskan bagaimana pengisian jabatan hakim Mahkamah Konsitutisi di Indonesia dengan melakukan perbandingan terhadap mekanisme pengisian jabatan hakim Mahkamah Konsitutisi di beberapa negara di dunia. Penelitian ini juga melakukan studi terhadap korelasi pengisian jabatan hakim Mahkamah Konstitusi dengan Independensi hakim Mahkamah Konstitusi dalam menjalankan fungsi dan wewenangnya. Artikel ini menyimpulkan bahwa ada tiga cara rekruitmen hakim konstitusi yang berlaku di beberapa negara. Pertama disebut, single body mechanism, mekanisme pengangkatan ini, eksekutif dapat menentukan seluruh anggota Mahkamah Konstitusi tanpa pengawasan lebih lanjut oleh cabang legislatif. Kedua, model cooperative appointment mechanisms; pengangkatan model ini menghendaki kerja sama di antara lembaga-lembaga dalam menentukan komposisi mahkamah atau organ sejenisnya. Ketiga, adalah model pengankatan representative, model ini melibatkan sejumlah lembaga negara. Sebagai contoh di Italia tiga dari Sembilan hakim konstitusi diajukan oleh Presiden, tiga oleh parlemen, dan tiga oleh Mahkamah Agung. Kata kunci: Pengisian Jabatan Hakim MK, Independensi, Perbandingan